Manajemen Tata Hubungan Komunikasi Kantor - Daud, Yusri M (Intelektualita: Journal of Education Sciences and Teacher Training, 2023)
Information will be difficult to receive if you do not have effective communication skills. Organizations such as offices must have effective office communication relations, in order to facilitate office information to stakeholders. The purpose of this study is to see how the form of office communication, organizing and implementing office communication and the obstacles faced in office communication. This research method is library research. The results of the research on office communication relations use the form of primary communication processes and secondary communication processes. Office organization is carried out by managers and public relations which are carried out communication relationships in a unidirectional and reciprocal manner. The implementation of organizational relations takes into account the principles and principles of communication. And barriers in communication are communication that obscures and changes the meaning of the sender such as language and cognitive differences, communication disorders, emotional disorders, and physical disorders.